Teletransporter and other troubles - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность", 2024)
The article is a commentary on the work of Alexey Kardash Teletransporter and Origami. It critically analyses the objections to the survival of the person in teleportation: about hidden dualism, about violation of cause-and-effect relations and about reflexive predicament. To answer, a reconstruction of Javier Hidalgo’s views presented in Survival of Teleportation is used. It is concluded that the objections raised by Alexey Kardash are problematic.